Country risk ratings and developing countries - Aşkar, Mahir (My University, 2008)
Son on yıllarda, küresel piyasalarda yaşanan finansal serbestinin sonucu olarak, dünya çapında yatırım olasılıkları artmış ve bu gelişme birçok fırsatla birlikte risklerin oluşmasına neden olmuştur. Bu yüzden ülke riski analizi çok önem kazanmıştır. Bu gelişmelere bağlı olarak, akademisyenler ve pratisyenler ülke risklerini doğru ve eksiksiz bir yolla ölçmek için farklı değerlendirme modelleri geliştirmişlerdir. Bu çalışmada, öncelikle, ülke riski kavramı ve literatürde kullanılan farklı tanımlar tartışılmıştır. Ardından, ülke riski değerlendirme yöntemleri olan nitel yaklaşım, derecelendirme ve nicel analiz irdelenmiştir. Bu yöntemlerden, derecelendirme yöntemi ülke risk derecelendirmeleri yayınlayan kurumlar ve derecelendirme yöntemleri esas alınarak kapsamlı bir biçimde incelenmiştir. Son olarak, Feder ve Just (1977)’nin modeline dayanan, gelişmekte olan ülkelerin borç öteleme davranışlarının nedenlerini anlamak için nicel bir analiz yapılmıştır. lke Riski, Ülke Riski Değerlendirmesi, Borç Öteleme

As a result of financial liberalization achieved in global markets in last decades, investment possibilities around the world have been boosted and this development has led to lots of opportunities and risks. Therefore, country risk analysis has gained significant importance. Afterward, academicians and practitioners have developed various assessment models to evaluate country risk in a precise and accurate way. This study first discusses the concept of country risk and its various definitions used throughout the literature. Then, country risk assessment methodologies: qualitative approach, ratings and quantitative analysis are considered. Of these techniques, ratings have been argued in detail with special reference to country risk rating entities and their rating methods. Finally, a quantitative study, which is based on the model introduced by Feder and Just (1977), in order to understand the reasons behind debt rescheduling behavior of developing countries, is conducted. Key words: Country Risk, Country Risk Assessment, Debt Rescheduling
Keywords: Borç Öteleme; Risk_Ekonomi; Ülke Riski